A Smart Transparency-Based Islamic Education Financing Strategy: Reconstructing Fiscal Planning in the Digital Era - Iska Fatmawati; Badrudin Badrudin; Qiqi Yuliati Zaqiah; Eva Saufana; Ade Abdullah Sidiq (Jurnal Iman dan Spiritualitas, 2026)
The main challenge of Islamic Education Management (IEM) today lies in the stagnation of financing innovation, which still relies on conventional schemes and remains highly dependent on government support. This condition has an impact on limited space for innovation, low flexibility in budget management, and minimal transparency and accountability in the financial governance of Islamic educational institutions. This study aims to deconstruct the strategic planning framework for Islamic education financing by integrating the Smart Transparency approach as a basis for adaptive financial governance in the context of digital transformation. The study uses a qualitative method, with a literature-based case study approach, to critically analyse various education financing management models and digital governance practices in the public sector. The results show that the effectiveness of financing Islamic educational institutions is largely determined by two main factors: the digitalization of the financial governance system and the diversification of non-governmental funding sources, including Islamic philanthropy, strategic partnerships, and educational entrepreneurial innovation. The novelty of this study lies in the formulation of the Digital Fiscal Accountability (DFA) model that integrates digital transparency, technology-based financial reporting, and participatory control mechanisms as a preventive strategy to minimize budget inefficiency and strengthen public accountability in the management of Islamic education financing.